2019
DOI: 10.1245/s10434-019-07803-z
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Peritoneal Mesothelioma: Patterns of Care and Survival in the Netherlands: A Population-Based Study

Abstract: BackgroundMalignant peritoneal mesothelioma (MPM) is a rare and aggressive disease. Recently, focus has shifted toward a more aggressive and multimodal treatment approach. This study aimed to assess the patterns of care and survival for MPM patients in the Netherlands on a nationwide basis.MethodsThe records of patients with a diagnosis of MPM from 1993 to 2016 were retrieved from the Dutch Cancer Registry. Data regarding diagnosis, staging, treatment, and survival were extracted. Cox regression analyses and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…On a global level, it is estimated that in 2018, mesothelioma caused about 25,500 deaths; however, not all countries report specific numbers of mesothelioma mortalities (Cancer Today, 2020;Odgerel et al, 2017). In general, mesothelioma affects the lining surrounding the lungs and the inside of the thoracic wall, but it can also affect other areas, such as the peritoneal surface or tunica vaginalis (de Boer et al, 2019). It is almost exclusively caused by exposure to asbestos minerals (Girgis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On a global level, it is estimated that in 2018, mesothelioma caused about 25,500 deaths; however, not all countries report specific numbers of mesothelioma mortalities (Cancer Today, 2020;Odgerel et al, 2017). In general, mesothelioma affects the lining surrounding the lungs and the inside of the thoracic wall, but it can also affect other areas, such as the peritoneal surface or tunica vaginalis (de Boer et al, 2019). It is almost exclusively caused by exposure to asbestos minerals (Girgis et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For inoperable or non-resectable patients, which are not suitable for the standard treatment, the guidelines recommend choosing SC treatment rather than palliative care ( 9 ). A recent study showed that better survival was independently associated with both the treatment combination of CRS plus HIPEC and surgery plus SC ( 17 ), although the overall survival of patients treated with SC plus CRS was approximately 1 year ( 18 ). If MPM patients cannot hold a beneficial prognostic factor, the treatment mode of CRS + HIPEC + adjuvant SC should be adopted ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the US Food and Drug Administration (FDA) approved the combination of nivolumab and ipilimumab as first-line treatment for unresectable MPM 4. For malignant peritoneal mesothelioma (MPeM), the median OS is about 6 months 5. For a long time, treatment options were identical to those for MPM.…”
Section: Introductionmentioning
confidence: 99%